Activation of GABAB2 subunits alleviates chronic cerebral hypoperfusion-induced anxiety-like behaviours: A role for BDNF signalling and Kir3 channels. (November 2016) - Lu, Yun; Li, Chang-jun; Chen, Cheng; Luo, Pan; Zhou, Mei; Li, Cai; Xu, Xu-lin; Lu, Qing; He, Zhi; Guo, Lian-jun
Abstract: Anxiety is an affective disorder that is commonly observed after irreversible brain damage induced by cerebral ischemia and can delay the physical and cognitive recovery, which affects the quality of life of both the patient and family members. However, anxiety after ischemia has received less attention, and mechanisms underlying anxiety-like behaviours induced by chronic cerebral ischemia are under-investigated. In the present study, the chronic cerebral hypoperfusion model was established by the permanent occlusion of the bilateral common carotid arteries (two-vessel occlusion, 2VO) in rats, and anxiety-related behaviours were evaluated. Results indicated that 2VO induced obvious anxiety-like behaviours; the surface expressions of GABAB2 subunits were down-regulated; Brain derived neurotrophic factor (BDNF), tyrosine kinase B (TrkB) and neural cell adhesion molecule (NCAM) were reduced; Meanwhile, the surface expressions of G protein-activated inwardly rectifying potassium (GIRK, Kir3) channels were up-regulated in hippocampal CA1 in 2VO rats. Baclofen, a GABAB receptor agonist, significantly ameliorated the anxiety-like behaviours. It also improved the down-regulation of GABAB2 surface expressions, restored the levels of BDNF, TrkB and NCAM, and reversed the increased surface expressions of Kir3 in hippocampal CA1 in 2VO rats. However, the effects of baclofen were absent in shRNA-GABAB2 infected 2VO rats. These results suggested that activation of GABAB2 subunits could improve BDNF signalling and reverse Kir3 channel surface expressions in hippocampal CA1, which may alleviate the anxiety-like behaviours in rats with chronic cerebral hypoperfusion. Highlights: Chronic cerebral hypoperfusion could induce anxiety-like behaviours in rats. Activation of GABAB2 subunits could alleviate the anxiety-like behaviours. Activation of GABAB2 subunits could improve BDNF signalling in 2VO rats. Activation of GABAB2 subunits could reverse Kir3 surface expression in 2VO rats.